Two New isoquinoline alkaloids from the bark of Alphonsea cylindrica King and their antioxidant activity - Obaid Aldulaimi, Ahmed Kareem; Abdul Azziz, Saripah Salbiah Syed; Bakri, Yuhanis Mhd; Nafiah, Mohd Azlan; Aowda, Saadon Abdulla; Awang, Khalijah; Litaudon, Marc (Elsevier, 2019)
Two new isoquinoline alkaloids, iraqiine (1) and kareemine (2), along with five known alkaloids, muniranine (3), kinabaline (4), O-methylmoschatoline (5), atherospermidine (6) and N-methylouregidione (7), were purified from the dichloromethane crude extract of Alphonsea cylindrica bark. The structures of these compounds were elucidated through extensive 1D and 2D NMR, IR and LC–MS studies and comparison with previously reported data. Compounds (1–5 and 7) were tested for their antioxidant activity using in vitro DPPH radical scavenging assay, and 1, 3 and 4 showed the highest antioxidant activities with IC50 values of 48.77 ± 1.01, 44.51 ± 1.12 and 64.28 ± 0.93 μg/ml, respectively.